Complexation of ditopic guests by cyclodextrins and derivatives. - E. A. Parrilla; P. R. Cabrer; F. Meijide; Vázquez J. Tato (ՀՀ ԳԱԱ հրատ.)
The complexation of ditopic guests by cyclodextrins and their higher degree derivatives is reviewed.
Keywords: Biology; Biochemistry